2022
DOI: 10.31080/asvs.2022.04.0460
|View full text |Cite
|
Sign up to set email alerts
|

Growth Modelling in Aseel Native Chicken

Abstract: Aseel, an important Indian native chicken breed, characterized by its aggressive behaviour, fighting ability and majestic gait is being utilized in India for developing crosses for backyard poultry farming. Therefore, information regarding its growth models is a pre-requisite which is yet not available. So, present investigation is first of its kind in India which was carried out to evaluate various non-linear models and to find out the best fitting growth model in Aseel. Data on body weights from second week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…They further reported that Bertalanffy model was the best model followed by Logistic model in Rhode Island Red and Rhode Island White random bred groups, which is quite similar to the present findings. Contrarily, Gompertz model was found to be the best model for describing growth in selected strain of Aseel chicken in combined sex data by Kumar et al (2022).…”
Section: Introductionmentioning
confidence: 96%
“…They further reported that Bertalanffy model was the best model followed by Logistic model in Rhode Island Red and Rhode Island White random bred groups, which is quite similar to the present findings. Contrarily, Gompertz model was found to be the best model for describing growth in selected strain of Aseel chicken in combined sex data by Kumar et al (2022).…”
Section: Introductionmentioning
confidence: 96%